Derechos humanos paradigma de un estado democrático constitucional - Atarama Lonzoy, Aldo Nervo (2024)
The national states, self-styled democratic, were formed guided by new principles. The current juridical-political crisis in the western world, especially in Europe, America and in our Peru, reflects the lack of recognition of human rights as the essence of this new society. The purpose of the study was to establish that human rights are the juridical-political foundation of the State as a whole. In this context it is analyzed: The Rule of Law. Its crisis generates a crisis of the principle of legality, as a paradigm of the old State. Constitutional Democracy. It has generated new paradigms and new principles contained in the current Constitution. The Constitution in the face of the Crisis of the Rule of Law has given way to a Constitutional Democratic State to establish new paradigms and principles such as fundamental rights such as human rights and develop fundamental rights as essential principles of this process of legal revolution that must be complied with by all and all institutions of public administration, in order to reaffirm this process of political legal transformation on the basis of the Constitution containing premises where the requirement of compliance is established or reaffirmed as there are new principles contained therein. Human Rights, highlighting that since 1945, when World War II ended, a process of legal revolution has begun, where the Rule of Law has entered into a legal-political crisis. The debate on the evaluated categories framed in the dimensions of Rule of Law, Democracy, Constitution and Human Rights in the treatment of human rights as a paradigm of a constitutional democratic state.